Expressiveness of real-time motion captured avatars influences perceived animation realism and perceived quality of social interaction in virtual reality - Fraser, A. D.; Branson, I.; Hollett, R. C.; Speelman, C. P.; Rogers, S. L. (Frontiers in Virtual Reality, 2022)
Using motion capture to enhance the realism of social interaction in virtual reality (VR) is growing in popularity. However, the impact of different levels of avatar expressiveness on the user experience is not well understood. In the present study we manipulated levels of face and body expressiveness of avatars while investigating participant perceptions of animation realism and interaction quality when disclosing positive and negative experiences in VR. Moderate positive associations were observed between perceptions of animation realism and interaction quality. Post-experiment questions revealed that many of our participants (approximately 40%) indicated the avatar with the highest face and body expressiveness as having the most realistic face and body expressions. The same proportion also indicated the avatar with the highest face and body expressiveness as being the most comforting and enjoyable avatar to interact with. Our results suggest that higher levels of face and body expressiveness are important for enhancing perceptions of realism and interaction quality within a social interaction in VR using motion capture.